Primary health care services: workplace spirituality and organizational performance - Albuquerque, I. F.; Cunha, R. C.; Martins, L.; Sá, A. B. (Journal of Organizational Change Management, 2014)
Purpose: The paper aims to study the influence of three dimensions of workplace spirituality (inner life, meaningful work and sense of community) on perceived and objective organizational performance in two primary health care settings: health centres (HCs) and family health units (FHUs), differing in terms of work organization. Design/methodology/approach: Data on workplace spirituality and perceived organizational performance were collected from a sample of 266 health care workers (doctors, nurses and administrative staff). Data on objective performance were obtained from the respective regional health authorities. Multiple regression, GLM, and tests of mediation were carried out. Findings: In both groups, perceived and objective organizational performance are predicted by sense of community. Additionally, FHUs presented significantly higher values in perceived and objective organizational performance, as well as sense of community and meaningful work. Finally, workplace spirituality and sense of community were found to mediate the relationship between work group and perceived and objective organizational performance. Research limitations/implications: The study's limitations include the convenience sample, as well as lack of control for the social desirability effect. Patient satisfaction surveys as well as the inclusion of predictive variables such as leadership should be considered in future studies. Practical implications: Primary health care services, and particularly FHUs, revealed the importance of workplace spirituality. Work teams with higher sense of community had higher performance results, which may therefore be an input in policy decisions regarding primary health care. Originality/value: This study compared the scores of workplace spirituality and perceived and objective organizational performance in two types of primary health care services, in a setting that approximates the quasi-field experiment. Workplace spirituality emerged as significantly mediating the relationship between work unit type and organizational performance.